DEVELOPMENT OF A BIRD SONG IDENTIFICATION MODEL USING A CONVOLUTIONAL NEURAL NETWORK (CNN) - Hannania, Nabila
Birds are a group of animals that have a very large diversity of species. However, this diversity is under threat of extinction due to human activities and natural phenomena. Identifying bird species that still exist in an ecosystem is an initial action that can be taken to protect this bird diversity. In this final project's research, a Convolutional Neural Network (CNN) model was built to automate the process of identifying bird species in a bird song sound record. In the experiments carried out, 24 CNN models were built, which had differences in architecture, feature extraction techniques, and the type of data used. There are three architectures used: AlexNet, DenseNet, and VGG. There are four feature